Local high-frequency vibration therapy following eccentric exercises reduces muscle soreness perception and posture alterations in elite athletes - Iodice, P.; Ripari, P.; Pezzulo, G. (European Journal of Applied Physiology, 2019)
Purpose: Exercise-induced muscle damage produces painful sensations (delayed onset of muscle soreness, DOMS). DOMS causes compensatory postural adaptations, which in turn affect athletes` walking and running gait biomechanics. It is still debated whether the postural changes are due to impaired proprioception or pain perception. To disambiguate between these two contrasting hypotheses, we designed a study that tested post-exercise postural adjustments in two groups of athletes: a group who was administered a vibration therapy (VT), to attenuate pain perception, and a control group. Methods: Thirty professional futsal players were tested on five different occasions: baseline, eccentric exercises (EE) session day, 24, 48 and 72 h after EE. Vibration therapy (120 Hz) was applied on legs muscles for 15 min in the experimental group, while no vibration was applied in the control group. The measurements included: isokinetic evaluation, stabilometric test, perceived soreness evaluation and serum levels of creatine kinase, and lactate dehydrogenase. Results: 48 h after EE, the control group showed changes in biomechanical parameters (antero-rotations of pelvis, p < 0.05). A substantial alteration in the hip kinematics was found, associated to a reduced contractile force (p < 0.01) and soreness perception. On the contrary, the VT group did not show any change in posture and pain perception. High-intensity VT decreases EE effects on muscle strength and DOMS. Conclusions: DOMS significantly changes athletes` posture; but postural changes disappear following a VT therapy that decreases pain perception. It is concluded that soreness perception is the main cause of postural changes and that its effects can be counteracted using VT therapy.